PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN INVESTIGATIVE SCIENCE LEARNING ENVIRONMENT (ISLE) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA - A Halim; Evendi Evendi; M Syukri; Fitria Herliana; Sri Wahyuni (Postgraduate, University of Mataram, 2021)
The aim of the research is to develop worksheets based on the ISLE approach to improve students' creative thinking skills. The method used in this research is research and development (R&D) and refers to the ADDIE development model. The student worksheets implementation design uses One Group Pretest-Posttest Design. The instruments used in this study were student worksheets assessment sheets, creative thinking skills test questions, student response questionnaires and teacher response questionnaires. Students' creative thinking skills were analyzed using the N-Gain test to see the improvement before and after the ISLE approach-based student worksheets was implemented. The results of the feasibility test in terms of the feasibility aspects of content, presentation and language obtained a percentage of 82, 88% indicated that the ISLE approach-based worksheets to improve creative thinking skills were very feasible to use. The results of the implementation of student worksheets based on the ISLE approach can improve students' creative thinking skills based on the N-Gain score in the high category. Teachers and students gave a very positive response to the ISLE-based student worksheets approach. The student worksheets based on the ISLE approach that has been developed statistically is feasible to use to improve students' creative thinking skills